Current principles of surgery for retroperitoneal sarcomas. Issue 1 (8th January 2018) - Fairweather, Mark; Gonzalez, Ricardo J.; Strauss, Dirk; Raut, Chandrajit P.
Abstract : Surgery for primary retroperitoneal sarcomas (RPS) often requires a technically challenging, en bloc multivisceral resection to optimize outcomes. Surgery may also be appropriate for patients with localized recurrent RPS. Anatomic considerations and tumor biology driven by histologic subtype may guide the extent of resection in patients with RPS. This review provides an overview of the current surgical principles for primary and recurrent RPS.